Ultrasonic and thermodynamic effects of self-association of aliphatic alcohols in cyclohexane. III. Secondary and tertiary butanols - BEBEK, K.; GRZYWNA, E.; ERNST, S. (Archives of Acoustics, 1997)
The ultrasound velocities in and densities of mixtures ofcyclohexane with 2-butanol{x1sec-C4H9OH+(1-x1)C6H12} and with 2-methyl-2-propanol{x1tert-C4H9OH+(1-x1)C6H12}have been measured at 293.15K. The adiabatic compressibility coefficients,βs=-1/V(∂V/∂p)s, and compressibilities, κs=-(∂V/∂p)s, as well as the excess molar volumes, VE, and free intermolecular lengths, L, were determined in the whole concentration range for both the systems studied. Using the measurement results in connection with literature data, the isothermal compressibility coefficients, βT=-1/V(∂V/∂p)T, and isochoric molar heat capacities, Cv, for the pure components were calculated. The above values were used to estimate the excess adiabatic compressibilities, κsE, of the mixtures under test accoring to the thermodynamically rigorous definitions recommended by Benson et al. The dependences of those excess functions on the mixture composition, reproduced by the Redlich-Kister equations, were compared and discussed in terms of the free intermolecular length and other factors affecting the self-association of alcohols (molecular geometry of the hydro-carbon chain and position of the OH group).